Conversion therapy in patients with colorectal liver metastases. Issue 8 (August 2021) - Villard, C.; Habib, M.; Nordenvall, C.; Nilsson, P.J.; Jorns, C.; Sparrelid, E.
Abstract: Background: The occurrence of colorectal liver metastases (CRLM) impairs prognosis, yet long-term survival can be achieved by enabling liver resection. This study aims to describe factors associated with conversion therapy leading to liver surgery and treatment outcome. Methods: A retrospective cohort study was conducted including all patients with CRLM discussed at multidisciplinary team conference at Karolinska University Hospital, Stockholm, Sweden, from 2013 to 2018. Factors associated with conversion therapy and outcome following conversion therapy were analysed with logistic regression and survival analyses. Results: Out of 1023 patients with CRLM, 100 patients (10%) received conversion chemotherapy, out of whom 31 patients (31%) subsequently underwent liver resection. Patients in whom conversion chemotherapy resulted in liver resection were younger (median age 61 vs. 66 years, p = .024), less likely to have a KRAS/NRAS-mutated primary tumours (25% vs . 53%, p = .039) and more likely to have received anti -EGFR agents (32% vs . 4%, p = .001) than patients progressing during conversion chemotherapy. The median OS for patients treated with conversion chemotherapy leading to liver resection was 24 months, compared to 14 months for patients progressing during conversion chemotherapy, p < .001. The OS for patients progressing during conversion chemotherapy was similar to patients given palliative chemotherapy, approximately 13 months. Conclusion: Conversion therapy offers a survival benefit in selected patients. Despite treatment advances, the majority of patients undergoing conversion chemotherapy never become eligible for curative treatment.